Identifikasi Makna Kafa’ah Dalam Perkawinan - Burmawi Junaidi; Nasaiy Aziz (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2022)
Kafa'ah is one of the important things in marriage, this is intended to produce harmony in the household so that it can be nurtured and the creation of a happy and harmonious household. Islam provides guidelines for choosing a partner based on four important criteria, namely religion, wealth, descent, and beauty. The different views were expressed by community leaders in Gampong Lada Village, namely expanding the meaning of kafa'ah in marriage by adding educational, position and job criteria in interpreting the meaning of kafa'ah. The problem in this thesis is how the meaning and criteria of kafa'ah in marriage and how the community leaders of Gampong Lada interpret kafa'ah and its criteria in marriage. The type of research used by the author in compiling this thesis is descriptive qualitative research. The results of this study indicate that the community leaders of Gampong Lada Village are very understanding about the meaning of kafa'ah in marriage, because the community leaders of Gampong Lada are very knowledgeable about religious knowledge. Gampong Lada community leaders interpret kafa'ah as equality, equivalence, and harmony between the prospective groom and the prospective bride when they want to get married. And the community leaders of Gampong Lada are of the view that for now the aspects of property, education, work, and position are very relevant in terms of kafa'ah, but even so, community leaders in Gampong Lada Village, Mutiara Timur District, and Pidie Regency do not rule out the religious aspect of the kafa issue. At this point, the community leaders of Gampong Pepper view that the religious aspect as the most important aspect of the meaning of kafa'ah in marriage.